2017
DOI: 10.1016/j.jvs.2016.06.110
|View full text |Cite
|
Sign up to set email alerts
|

Patients with diabetes differ in atherosclerotic plaque characteristics and have worse clinical outcome after iliofemoral endarterectomy compared with patients without diabetes

Abstract: Patients with DM who undergo surgical revascularization for PAD with the use of thromboendarterectomy or remote endarterectomy have a more calcified atherosclerotic plaque and an increased incidence in composite cardiovascular events but no increase in TVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…In female patients, the presence of OM was associated with diabetes. All the diabetic women had OM, corroborating the previously published data reporting a higher prevalence of calcified plaques and OM in a plaque in diabetic patients (16,36). Vascular calcification resembles osteogenesis, when vascular smooth muscle cells (VSMCs) express bone-associated proteins (e.g., osteocalcin, osteopontin, bone sialoprotein, and alkaline phosphatase) that promote the calcification processes (37).…”
Section: Discussionsupporting
confidence: 85%
“…In female patients, the presence of OM was associated with diabetes. All the diabetic women had OM, corroborating the previously published data reporting a higher prevalence of calcified plaques and OM in a plaque in diabetic patients (16,36). Vascular calcification resembles osteogenesis, when vascular smooth muscle cells (VSMCs) express bone-associated proteins (e.g., osteocalcin, osteopontin, bone sialoprotein, and alkaline phosphatase) that promote the calcification processes (37).…”
Section: Discussionsupporting
confidence: 85%
“…6 Diabetic patients are known to have a high percentage of calcified plaques, but no decline was detected over time in this diabetes specific plaque feature. 10 One possible explanation is that the persistent high prevalence of severely calcified lesions within patients with diabetes might be an effect of statin treatment. Statin use has been associated with increased calcifications of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…9 It is unknown, however, whether this reduction in vulnerable plaque features and secondary cardiovascular events also occurs in IFE patients with diabetes who are known to have more severely calcified plaques. 10 Moreover, in the Netherlands, patients with claudication are first treated conservatively with supervised walking therapy before invasive therapy. It is unclear whether these treatment strategies have influenced outcomes for diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, van Haelst et al found that patients with diabetes had more calcification in atherosclerotic plaque and a higher occurrence of secondary cardiovascular events than patients without diabetes. 7 Even though we can distinguish atherosclerotic plaque in diabetic and nondiabetic patients from morphologic fields, the effect of diabetes on gene expression in atherosclerotic plaque is not fully understood.…”
Section: Introductionmentioning
confidence: 99%